Retrieval of vegetation biophysical variables from CHRIS/PROBA data in the SPARC campaing - Gandia, S.; FernÃ¡ndez, G.; GarcÃa, J. C.; & Moreno, J. (Proceedings of the 2nd CHRISProba Workshop ESAESRIN Frascati Italy 2830, 2004)
In the context of the SPARC campaign, a total of 10 different view angle images are available from CHRIS/PROBA data, all of them acquired in Mode 1 (62 spectral bands). These data make possible to test some of the algorithms developed to extract vegetation biophysical variables from high-spectral resolution data with multiangular capabilities, in the context of the SPECTRA mission. Validation of retrievals with the large dataset of ground measurements that is available in SPARC represents a unique opportunity to exploit the innovative CHRIS/PROBA data. Variability in ground measurements was evaluated by statistical techniques, according to the sampling used in the data collection. Two different approaches have been followed in the retrieval of vegetation biophysical variables. First, a large number of spectral indices have been tested with the available spectral information. The second method used is based on model inversion techniques. A combination of adapted versions of PROSPECT 1, and SAIL 2, models have been tested in forward mode, by using all available ground measurements to reproduce the top-of-canopy reflectance, and then compare these forward simulations with atmospherically corrected CHRIS data.

An investigation into robust spectral indices for leaf chlorophyll estimation - Main, Russell; Cho, Moses Azong; Mathieu, Renaud; OâKennedy, Martha M.; Ramoelo, Abel; Koch, Susan (ISPRS Journal of Photogrammetry and Remote Sensing, 2011)
Quantifying photosynthetic activity at the regional scale can provide important information to resource managers, planners and global ecosystem modelling efforts. With increasing availability of both hyperspectral and narrow band multispectral remote sensing data, new users are faced with a plethora of options when choosing an optical index to relate to their chosen or canopy parameter. The literature base regarding optical indices (particularly chlorophyll indices) is wide ranging and extensive, however it is without much consensus regarding robust indices. The wider spectral community could benefit from studies that apply a variety of published indices to differing sets of species data. The consistency and robustness of 73 published chlorophyll spectral indices have been assessed, using leaf level hyperspectral data collected from three crop species and a variety of savanna tree species. Linear regression between total leaf chlorophyll content and bootstrapping were used to determine the leafpredictive capabilities of the various indices. The indices were then ranked based on the prediction error (the average root mean square error (RMSE)) derived from the bootstrapping process involving 1000 iterative resampling with replacement. The results show two red-edge derivative based indices (red-edge position via linear extrapolation index and the modified red-edge inflection point index) as the most consistent and robust, and that the majority of the top performing indices (in spite of species variability) were simple ratio or normalised difference indices that are based on off-chlorophyll absorption centre wavebands (690â730 nm).
Keywords: Leaf level reflectance; Leaf chlorophyll; Red-edge; Vegetation indices; Photosynthetic activity

The IndexDatabase - Henrich, V.; Krauss, G.; Götze, C.; Sandow, C. (2011)